Influence of ethephon on ripening and quality of winter tomato fruit harvested at different maturity stages (Bangladesh Journal of Agricultural Research, 2016)
An experiment taking tomato fruits (cv. BARI Tomato-14) of three maturity stages (mature green stage, breaker stage and half ripen stage) and four ethephon levels [control (distilled water spray), 500, 750 and 1000 ppm] was carried out at the laboratory of plant physiology section of Horticulture research centre, Bangladesh Agricultural Research Institute) during February 14, 2013 to February 27, 2012 to find out the suitable stage of fruit maturity for post harvest application of ethephon (ethrel) for tomato ripening. The source of ethrel was Spectrum (ethephon 39%) manufactured in the United States of America. Treatment with 500 - 1000 ppm ethephon hastened ripening of tomato by 4 days in mature green stage but by 2 and 4 days in breaker stage tomatoes when compared with control fruits. The highest value of rotting was shown by half ripen tomatoes. The 1000 ppm ethrel gave the maximum rotting irrespective of maturity stages. However, the maximum weight loss and shelf life were found in green mature tomatoes. The shelf life of tomato fruits of green mature and breaker stage tomatoes treated with 500 and 750 ppm was also high. The percentage of rotting and weight loss was increased with gradual advancement of time. The highest value of weight loss and shelf life was recorded in green mature tomatoes without ethephon and with 500 and 750 ppm ethephon treatment. The highest value of vitamin-C, TSS and titrable acidity were shown by half ripen and pH by green mature tomatoes at different days of storage. The ethephon concentration of 750 ppm the gave maximum vitamin-C at 6 and 9 days of storage but 1000 ppm gave the maximum TSS% followed by 750 ppm ethephon. The ethephon @ 750 ppm produced the maximum TSS at 9 day of storage in mature green tomatoes but in breaker and half ripen stage tomatoes 750 ppm ethephon gave TSS identical to 1000 ppm at different days of storage. The residue level of ethrel in tomato fruits treated with all ethephon concentrations at 3 and 5 days of storage was below 2 mg/kg which is safe for human health. Therefore, treated tomatoes should be consumed after 3 days of ethephon application.Bangladesh J. Agril. Res. 40(4): 567-580, December 2015